(untitled) (Islas, 2026)
Introduction: This article examines the expression of emotional intensity through metaphorically charged verb–noun collocations in Peninsular Spanish and contemporary French, considering their cognitive, discursive, and cultural implications within a contrastive framework. It is based on the hypothesis that intensification is not an exclusively lexical phenomenon, but rather the result of constructional configurations in which aspectual, metaphorical, and syntactic factors interact. Methods: The study is based on a corpus of 311 verb + noun collocations belonging to the domain of emotions. A qualitative and semi-quantitative methodology is adopted, combining manual analysis with systematic categorization procedures. The units are classified according to aspectual values (inchoative, durative, iterative, culminative, and hybrid), metaphorical domains, emotional classes, and syntactic constructions, within a non-symmetrical contrastive approach that avoids forced equivalences between languages. Results: The data reveal differentiated patterns between the two languages. In the Spanish corpus, metaphors of externalization, dynamism, and release predominate, associated with inchoative or culminative configurations. In the French corpus, by contrast, more introspective, progressive, or accumulative images are observed, linked to durative or stative values. These tendencies suggest different modes of discursive conceptualization of emotional intensity, depending on the corpus analyzed. Conclusions: Emotional intensification emerges from the interaction between verb, aspect, metaphor, and syntax, giving rise to contrastive discursive models that function as interpretive frameworks in the intercultural analysis of emotions and in translation pedagogy.